Vers une judiciarisation du Conseil des ministres? - Lemieux, Denis; Savard, Esther (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1985)
In Canada on the federal and provincial levels, the Cabinet plays a powerful role as the supreme administrative agency. Unlike its British counterpart, a more conventional body, Canadian cabinets are invested with wide-ranging statutory powers of decision. In this capacity, the Cabinet makes decisions affecting the rights of individuals, groups and corporations. Under the duty to act fairly according to rules developed in British and Canadian caselaw, the Cabinet should, in such circumstances, be required to act quasi judicially. However, as a political entity, the Cabinet can hardly be characterized as a tribunal and the courts hesitate to impose an adversary system upon such an institution. Nevertheless, in several instances, Canadians have had the power to assert that the Cabinet act fairly when dealing with individual rights. The advent of charters of right is another incentive to treat the Cabinet as any agency of the Crown or other public authority bound by the principles of fundamental justice. The authors submit that this legal development may modify cabinets' decision-making powers and make them more open to external representations.